MOLECULAR IDENTIFICATION OF PROBIOTIC YEAST STRAINS AND THEIR CHARACTERIZATION - Lakshmi Ragavan, Mangala; Das, Nilanjana (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective The objective of the present study was to identify the potential yeast isolates at themolecular level and evaluate their probiotic characteristics. Methods Molecular characterization was done for 5 potential probiotic yeast strains. In vitro assays have been conducted to evaluate the probiotic properties such as NaCl tolerance, autoaggregation and co-aggregation. Haemolyticactivity, urease activity and cytotoxicity tests were carried out for safety assay during the characterization of yeast strains. Results In this study, the yeast strains viz. LM,MR,GOI,GII2and WI were identified at molecular level and named as Yarrowialipolytica VIT-MN01, Kluyveromyces lactis VIT-MN02, Lipomyces starkeyi VIT-MN03, Saccharomycopsis fibuligera VIT-MN04, Brettanomyces custersianus VIT-MN05 respectively. Maximum autoaggregation and coaggregationwere noted in case of Lipomyces starkeyi VIT-MN03, Saccharomycopsis fibuligeraVIT-MN04, and Brettanomyces custersianus VIT-MN05. In vitro toxicity assay was performed and all the yeast strains showednon-toxic nature. Conclusion Five yeast strains have been studied for their probiotic characteristics and identified at molecular level. Out offive yeast strains, three strains showed maximum adhesion ability,which is a prerequisite for colonization and protection of gastrointestinal tract. All the yeast strains are validated as a safe bioresources because of their non - hemolytic activities and non-production of urease. It can be concluded that the identified yeast strainscan serve as promising probiotics in various fields offood industry.